2018
DOI: 10.1002/adfm.201806460
|View full text |Cite
|
Sign up to set email alerts
|

Ten States of Nonvolatile Memory through Engineering Ferromagnetic Remanent Magnetization

Abstract: Emerging nonvolatile multilevel memory devices have been regarded as a promising solution to meet the increasing demand of high-density memory with low-power consumption. In particular, decimal system of the new computers instead of binary system could be developed if ten nonvolatile states are realized. Here, a general remanent magnetism engineering method is proposed for realizing multiple reliable magnetic and resistance states, not depending on a specific material or device structure. Especially, as a proo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…[ 2,21 ] Recent studies also showed the multi‐level states in 6 µm diameter in‐plane MTJs through the magnetic field sweeping. [ 22 ] However, the current‐induced switching is more advantageous in today's memories allowing a shared path for writing‐reading operation, but requiring the perpendicular anisotropy to reduce the writing current. Furthermore, from an industrial manufacture point, the fabrication of multi‐level switching in single p‐MTJ is much easier than previous efforts as connecting several MTJs in series or stacking MTJs vertically.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 2,21 ] Recent studies also showed the multi‐level states in 6 µm diameter in‐plane MTJs through the magnetic field sweeping. [ 22 ] However, the current‐induced switching is more advantageous in today's memories allowing a shared path for writing‐reading operation, but requiring the perpendicular anisotropy to reduce the writing current. Furthermore, from an industrial manufacture point, the fabrication of multi‐level switching in single p‐MTJ is much easier than previous efforts as connecting several MTJs in series or stacking MTJs vertically.…”
Section: Resultsmentioning
confidence: 99%
“…[ 16,18 ] In MTJs, the current driven DW motion was reported in the U shape [ 19 ] and T shape [ 20 ] nanowires with a very large aspect ratio, which cannot be directly implemented into memories since an aspect ratio close to 1 is expected. [ 21 ] The multi‐domain state was lately revealed in in‐plane MTJs through magnetic field sweeping, [ 22 ] but the demonstration of current‐driven multi‐state with perpendicular anisotropy is required for memory application. The magnetic domain properties of perpendicular CoFeB have been studied in unpatterned thin films.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we can conclude that through controlling the PMA via electrical field driven oxygen ion migration, the spin‐orbit torque induced magnetization switching can be controlled. Furthermore, the memristive behavior that arises from the SOT‐induced multilevel intermediate states due to partial magnetization switching also provides an attractive method for designing multi‐bit data storage43,44 and neuromorphic computing 45–47…”
Section: Resultsmentioning
confidence: 99%
“…Thereby, this system has great potentials in multinary data storage and information multiplexing. The state-of-theart strategies for the generations of multilevel magnetic states mainly use the external magnetic or electric field in magnetic multilayer, multiferroic material, artificial ferromagnetic/ferroelectric heterostructure systems [8,48,49]. Some uses light to control the carrier in materials, which relies on the detailed magnetic structures such as the fourfold magnetic anisotropy in (Ga,Mn)As [50], and to use the light-induced spin-polarized currents in the magnetic spin-valve structure ([Co/Pt]/Cu/GdFeCo) [51].…”
Section: All-optical Multistate Magnetizationmentioning
confidence: 99%
“…The demand for the ever-growing vast density of magnetic storage, however, has triggered a new upsurge for avenues to attain multilevel states in these magnetic systems. Tremendous research endeavors in this regard, embracing ingenious magnetic characteristic or resistance switching design, have been devoted toward multiplexing the magnetization/resistance into diverse levels with a controllable polarization orientation [5][6][7][8]. Despite extensive effects and significant progresses, it is still challenging to resolve the limited states, slow switching speed and low-energy efficiency issues dictated by external electrical or magnetic fields.…”
Section: Introductionmentioning
confidence: 99%